THE RELATIONSHIP BETWEEN GERMAS PROGRAM AND HYPERTENSION CONTROL IN LHOKNGA PRIMARY HEALTH CARE, ACEH BESAR, INDONESIA - Mustaqim, Liza; Azwar, Eddy; Arifin, Vera Nazhira; Septiani, Riza (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Hypertension is a global issue since its prevalence increased in line with changes in lifestyle, especially in dietary patterns and low physical activity. In Indonesia, “the Healthy Living Movement” or “Gerakan Masyarakat Hidup Sehat” (GERMAS) Program which was launched in 2016 consists of seven pillars including physical activity, consumption of fruits and vegetables, no smoking, no alcohol, early detection of disease, environmental health, and latrines usage. The aim of this study is to analyze the relationship between GERMAS Program and hypertension control among patients in Lhoknga Primary Health Care (PHC) in Aceh Besar, Indonesia. Method: This study is a cross-sectional, with the subjects of 60 patients with hypertension in Lhoknga PHC, chosen by proportional sampling. Data were collected by interview and observation of blood pressure patients between 8 March and 26 March 2021. Data were analyzed univariate and bivariate using chi-square with significance p0.05. Results: The results show relationship between physical activity (p=0.019), consumption of fruits and vegetables (p=0.001), no smoking (p=0.038), routine health check (p=0.001), and hypertension control. Recommendation: Health workers in PHC are suggested to educate the community including patients with hypertension about GERMAS Program and support them in starting and maintaining a healthy living movement. Massive health education and socialization about GERMAS through various media are also essential social marketing in improving health in the community.